Collapse of Late Permian chert factories in the equatorial Tethys and the nature of the Early Triassic chert gap - Yang, F.; Sun, Y. D.; Frings, P. J.; Luo, L.; E, J. W.; Wang, L. N.; Huang, Y. F.; Wang, T.; Müller, Johann; Xie, S. C. (Earth and Planetary Science Letters, 2022)
Permian chert successions were geographically extensive, spanning from the palaeoequator to the northern high latitudes. Large-scale chert production was abruptly terminated in the latest Permian, resulting in a multi-million-year “chert gap” in the Early Triassic. In order to constrain the tempo of chert production changes and understand their nature, we combine proxy data with Si box model analyses and focus on the Talung Formation of South China—the most representative Upper Permian siliceous unit in the equatorial Tethys. Two deepwater sections from the northern margin of the Yangtze Platform were investigated, showing that bedded cherts had already become less common in the Clarkina changxingensis conodont zone. The waning of chert production coincided with water column deoxygenation and an increase in carbonate and siliciclastic components in the late Changhsingian. The final collapse of the chert factory in South China predated the negative δ13C excursion and climate warming but coincided with a sharp decrease in primary productivity. Together with Si box model output, we suggest that warming-induced expansion of the oceanic dissolved silica inventory (and decrease in burial efficiency) alone cannot maintain a multi-million-year chert gap. Instead, a loss of siliceous biomass during the end-Permian crisis is the primary cause of the Early Triassic chert demise.
CRIS-Team Scopus Importer:2022-11-04
Keywords: chert gap; conodont; end-Permian mass extinction; Si box model; Talung Formation